REVITALISASI TAMAN HARMONI UNTUK MENARIK KUNJUNGAN WISATAWAN Revitalization of Taman Harmoni to Attract Tourist Visits - Gabriel Brilliantanti; Ety Dwi Susanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the effectiveness of physical revitalization at Taman Harmoni Surabaya (the former Keputih landfill) in transforming its destination image and enhancing its urban eco-tourism appeal. Using a descriptive qualitative case-study method, data were collected through interviews, observation, and documentation involving three purposively sampled informants — individuals familiar with the area’s history and first-time visitors. Data were analyzed using the interactive model of Miles et al. (2014), comprising data reduction, data display, and conclusion drawing. The results indicate that landscape transformation through aesthetic elements, such as Tabebuya trees, thematic continent-based zones, and a bamboo-forest culinary area, effectively eliminates past negative stigma associated with the site’s history as a landfill. Organic user-generated content on Instagram and TikTok further amplified the destination’s digital exposure, attracting domestic and international visitors. This physical and digital optimization has established Taman Harmoni as a healthy, sustainable public space and a determining factor in increasing tourist visits.